GAYA TARI PASOMBAHAN KREASI DI KECAMATAN BANGKINANG KOTA KABUPATEN KAMPAR PROVINSI RIAU - Meizul Ofriananda; Herlinda Mansyur; Indrayuda Indrayuda (FBS Universitas Negeri Padang, 2016)
Abstract This research aims to find out and describe the styles of the Pasombahan Kreasi* dance at Bangkinang Kota Municipality Kampar Regency Riau Province. The design of the research was qualitative by using the descriptive method which included observation, interview, and documentation. First, the researcher did the observation and interview various sources of information. Later, he examined the documents about related data and information in the field. The research was done at Bangkinang Kota Municipality Kampar Regency Riau Province.The result of analysis shows that there are four styles in the Pasombahan* dance. First, the hands, feet, and head are dominantly in motion for each move and the body moves along with the motion of the hands or feet. They can be seen in the moves of sepok*, ulu limpiong*, gletek*, klenjek*, punte tali bowuok*, elo somba*, and sombah*. Second, the moves dominantly go to the front direction such as in the moves of sepok, punte tali bowuok, elo somba and sombah. The moves, later, go along with the body like in the moves of ulu limpiong, gletek, and klenjek. Third, the rhythm of the dance is in count of 1×8 such as in the moves of sepok, ulu limpiong, gletek, klenjek, punte tali bowuok, and elo somba. Meanwhile, the rhythm in the move of sombah is in the count of 2×8. Four, the quality of the moves in the dance is determined by space, time, and power. The space in the moves of sepok, klenjek, elo sombah, and sombah is a direct and big space. Meanwhile, the space in the moves of ulu limpiong, gletek, and punte tali bowuok is an indirect and big space. In term of time, it is done continuously in the moves of sepok, ulu limpiong, and klenjek while it is done suddenly in the moves of gletek, punte tali bowuok, and sombah. In the move of elo sombah, it is done directly. Finally, in term of power, the moves of sepok and gletek are done in big power while the moves of ulu lipiong, klenjek, punte tali bowuok, elo somba, and sombah are done in light power. Those results show that the styles in the Pasombahan dance are the combination of Minangkabau martial art dance and Bangkinang-Malay version.Keywords: Style. Dance. Pasombahan. Creation